Multiscale simulation methods for nanomaterials (Wiley-Interscience, 2008)
This book stems from the American Chemical Society symposium, Large Scale Molecular Dynamics, Nanoscale, and Mesoscale Modeling and Simulation: Bridging the Gap, that delved into the latest methodologies and applications for largescale, multiscale, and mesoscale modeling and simulation. It presents real-world applications of simulated and synthesized materials, including organic-, inorganic-, bio-, and nanomaterials, and helps readers determine the best method for their simulation. It gets novices up to speed quickly and helps experienced practitioners discover novel approaches and alternatives.